Peningkatan Hasil Belajar Peserta Didik Pada Tematik Terpadu Dengan Menggunakan Model PBL di Kelas IV SD - Abdul Khairi; Yalvema Miaz (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to describe the increase in student learning results on thematic Integrated Learning Model using Problem Based Learning in class IV SDN 14 Gadut Tilatang Kamang. This research used a qualitative and quantitative approach. This type of research i.e. Research Action class (PTK). The subject of research is the grade IV SDN 14 Gadut Tilatang Kamang.  Feed as many as 20 students. Research conducted two cycles. The design of the research include, (1) planning, (2) implementation, (3) and (4) observation of the reflection. The results showed an increase in: a) the RPP cycle I 85,93%  (SB) Cycle II 93,75% (SB) b) implementation on aspect of teacher cycle I 84,71% (SB), a cycle II 96,42% (SB) c) Implementation on aspect students cycle I 85.71% (B) and Cycle II 96,42% (SB) d) student learning outcomes Cycle I 75,46 (B), cycle II 87 (A). Thus the model of Problem Based Learning can improve the learning results of integrated thematic grade IV SDN 14 Gadut Tilatang Kamang.